Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Literasi Keuangan Pegawai di Kantor Sekretariat Daerah Kabupaten Nias - Nofelman Duha; Maria Magdalena Bate’e; Idarni Harefa; Kurniawan S. Zai (Visi Sosial Humaniora, 2024)
Employees at the Nias Regency Regional Secretariat Office have different understandings about financial literacy. Some employees are trapped in fraudulent investments and there are still many employees who have consumerist habits, namely buying things based on desire, not need. This research aims to determine the influence of age, gender, education and income factors on the level of financial literacy of employees at the District Regional Secretariat Office. The data collection method in this research uses primary data obtained from filling out questionnaires with 51 employee respondents at the Nias Regency Regional Secretariat office as well as secondary data obtained from journals related to this research. The data analysis methods used are validity test, reliability test, correlation coefficient test, determinant coefficient test, normality test, heteroscedasticity test, multiple linear regression test, T test and F test. The results of this study show that the factors of age and education have a positive and significant effect on the level of financial literacy of employees at the Regional Secretariat Office of Nias Regency, while the factors of gender and income do not have a positive and significant effect on the level of financial literacy of employees at the Regional Secretariat Office of Nias Regency. Simultaneously, the factors age, gender, education and income have a 76.4% influence on the level of employee financial literacy, while the other 23.6% is influenced by other variables not included in the research.